Trial of Lime Juice on Mozzarella Cheese Making - Purwadi Purwadi (Faculty of Animal Science Universitas Brawijaya, 2007)
This research which had a purpose for studying a potency of lime juice as acidifier in the making of Mozzarella cheese was done to know its influence on Mozzarella cheese physical quality. The method used in this research was Completely Randomized Design. Optimum concentration lime juice as acidifier for making Mozzarella cheese repeated 6 times had variation treatment, including : P1 = 0.5%, P2 = 1.0%, P3 = 1.5%, and P4 = 2.0% (w/v). All variables examined were rendement, meltability, stretchability, and elasticity. Variation analysis on rendemnet and strechability of Mozzarella cheese showed that those variationÂ of lime juice gave no significant difference effect (P>0,05) on Mozzarella cheese physical quality. But, those treatments gave very significant difference effect (P<0,01) on meltability and gave significant difference (P<0,05) on elasticity Mozzarella cheese. The range of result of cheese rendement was about 11,76-12,17%. The highest meltability was resulted from the use of 2.0% lime juice and its value was 8,57. The highest elasticity was from the highest concentration of lime just 2,0% and its value was 63,64% and based on statistic gave significant defference (P<0,05) compared with other concentration. Â Keywords : lime juice, Mozzarella cheese, acidifier